BANTUAN TEKNIK DAN PERENCAAAN PEMBIAYAAN REVITALISIASI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO KAMPUNG BUNIKASIH DESA BUKANAGARA KECAMATAN CISALAK - Novandri Tri Setioputro; Muhtar Kosim; Kasda Kasda; Sugeng Sutikno; Ari Ajibekti Masriwilaga (Universitas Majalengka, 2023)
Bunikasih Rural community and the Faculty of Engineering at the University of Subang took the initiative to build the Bunikasih Micro Hydro Power Plant (MHP) in 2013, with financial support from CRS BNI Go Green. The Bunikasih MHP is situated in the Bunikasih area of Cupunagara Village, Cisalak District, Subang Regency, West Java Province, Indonesia. The Bunikasih MHP was initially utilized to supply electricity for the Bunikasih Rural community, which at the time was off grid. In 2018, an earthquake occurred therefore it made MHP Bunikasih malfunctioning. The Engineering Faculty team and the Bunikasih community undertook Focus Group Discussion/FGD activities prior to the MHP Bunikasih damage survey. The results of the FGD activities are the revitalization of the Bunikasih MHP so that it can operate again. It was also proposed that MHP Bunikasih is to be utilized to support the increase in the processing of agricultural production. The survey revealed that Bunikasih MHP suffered heavy damage. The channel was cracked and broken. The penstocks was bent. The roof of the turbine house was collapsed. The generator and electrical controls were fried. Damage to civil buildings can be repaired by making a new building structure in the damaged part. The bent pen stock is repaired by cutting the bent part and replacing it with a new pipe. A new roof is installed to the turbine house. The generator and control system are fixed and new components are installed. In general, all components of the Bunikasih MHP that were damaged can be repaired and revitalized. The cost for the revitalization is Rp. 213,700,000.00.